Protein-Silica Hybrid Submicron Particles: Preparation and Characterization - Vega-Chacón, Jaime [UNESP]; Tarhini, Mohamad; Lebaz, Noureddine; Jafelicci, Miguel [UNESP]; Zine, Nadia; Errachid, Abdelhamid; Elaissari, Abdelhamid (Springer Nature, 2020)
Purpose: Hybrid nanoparticles are an interesting type of particles currently employed in nanomedicine. They can combine the therapeutic and diagnostic functions of their components into one single nanosystem and therefore, can be tweaked according to their applications and desired results. The purpose of this work is to develop an easily tuned nano-system of bovine serum albumin-silica hybrid nanoparticles. Methods: BSA nanoparticles were prepared by nanoprecipitation process using water as the solvent phase and ethanol as the non-solvent. Silica was produced through a sol–gel process and deposited inside the BSA nanoparticles via template deposition. The effect of initial concentrations of raw materials on the structure and colloidal properties of the system was evaluated using FTIR, TGA, TEM, and zeta potential measurements. Results: A hybrid structure of BSA-silica was obtained. The results suggest that the particles size, isoelectric point and silica content of the hybrid nanoparticles can be easily tuned by controlling adequately the concentration of TEOS and ammonia. Conclusion: Our method can be considered as a novel approach for hybrid nanoparticle synthesis. To our knowledge, we report for the first time the synthesis of silica-BSA hybrid particles with a non-core–shell structure. In addition, we proved that that the particles size, isoelectric point and silica content of the hybrid nanoparticles can be easily tuned by controlling adequately the concentration of TEOS and ammonia.
Keywords: BSA; Characterization; Hybrid nanoparticles; Silica